Difficulties of Non-Arabic Study Program Students in Arabic Teaching and Learning Process at ITB AAS Indonesia - Nur Fitria, Tira (Sekolah Tinggi Agama Islam Al-Hikmah Pariangan Batusangkar, West Sumatra, Indonesia., 2023)
This study investigates the difficulties of Non-Arabic study program students in Arabic learning at ITB AAS Indonesia. This research uses descriptive qualitative. This study involves 60 students of the Economy Sharia study program. The analysis shows internal and external factors of students’ difficulties in Arabic learning. The internal factors are 1) difficulty in writing Hijaiyah letters at the beginning of, in the middle, and at the end of the sentence. 2) difficulty in writing Hijaiyah letters in computer typing because it must have an Arabic Typesetting font. 3) belief that writing Arabic letters is more difficult than writing Latin letters, 4) difficulty in reading recitation (Tajwid). 5) belief that learning Arabic is more difficult than Indonesian and English. 6) belief that many Mufrodat includes Isim, Fi'il, and Harf. 7) many rules for changing words and writing an Arabic sentence. Besides, external factors are 1) many foreign expressions or Arabic terms that are different from Indonesia. 2) lack of learning media of Arabic textbooks. 3) lack of facilities in the language laboratory. 4) lack of environment, association, social, and culture in learning Arabic. 5) lack of self-support and motivation in learning Arabic. 6) influence of the first language (regional) and the second language (Indonesian). 7) Arabic learning time is short to 1 week. 8) a lot of Arabic material in one semester. 9) too many students in a class. 10) situation in the Arabic class is not conducive.